Pengembangan Alat Seismograf Sederhana Sebagai Media Pembelajaran Materi IPS di SD - Nur Alawiyah; Tuti Istianti; Muh. Husen Arifin (Journal Civics and Social Studies, 2021)
Learning media is one of the essential components in the world of education. In its use, learning media is used to explain and convey information related to the learning that is being carried out. Learning media helps teachers to be able to attract students' attention when learning. The cause of this is to take a look at the impact of using simple seismograph learning media on the impact of Indonesia's geographical location in elementary school. Social studies learning in this elementary school needs an update so that when delivering material it does not only use the lecture method which results in making students bored and not involved when learning. Therefore, researchers made this research so that teachers can always develop a renewal, namely by developing learning media in the form of a simple designed seismograph. The results of this study can be concluded by developing a simple seismograph tool as a learning medium for social studies material in elementary schools about the impact of Indonesia's geographical location on the sample material taken, namely earthquakes. It can be stated that in the use and manufacture of this simple seismograph tool, it is able to make students involved in learning, make students curious when studying and can motivate students to learn actively. Its simple construction is an added value in the development of this learning media because it is suitable for use for elementary school children.Keywords: Learning Media, Seismograph Tools, Social Studies Material, Geographical Impact